Location Planning as a Success Factor in Automotive Business: a Study at Purnama Mobilindo, Solok City - Rino Esa Maha Putra; Yance Gafar; Lusiana Lusiana (Sean Institute, 2026)
Business location planning is a crucial factor influencing business success, particularly in the competitive automotive sector, as strategic location not only determines the number of customers but also impacts operational efficiency and business competitiveness. This study aims to analyze the influence of location on the performance of Purnama Mobilindo in Solok City using a case study method and qualitative and quantitative approaches. Data were collected through interviews with the owner and employees, direct observation of the business environment, and questionnaires with customers to obtain a comprehensive picture of the influence of location on operations, sales, and customer satisfaction. The results show that strategic location selection has a significant impact on business performance, where easy accessibility, proximity to economic activity centers, and visibility from main roads increase the number of customers and their loyalty. In addition, a supportive environment, including supporting facilities and location security, also strengthens the customer experience and encourages increased sales. These findings confirm that location planning is not merely a geographical consideration, but a crucial factor in the success of automotive businesses, as selecting the right location can increase turnover, strengthen the business's position in the local market, and become an important strategy for long-term business development.